Anaphylaxis in children. Issue 3 (June 2016) - Farbman, Karen S.; Michelson, Kenneth A.
Abstract : Purpose of review: Anaphylaxis is a serious allergic reaction that can be life threatening. We will review the most recent evidence regarding the diagnosis, treatment, monitoring, and prevention of anaphylaxis in children. Recent findings: Histamine and tryptase are not sufficiently accurate for the routine diagnosis of anaphylaxis, so providers should continue to rely on clinical signs. Platelet-activating factor shows some promise in the diagnosis of anaphylaxis. Intramuscular is the best route for epinephrine administration for children of all weights. Glucocorticoids may reduce prolonged hospitalizations for anaphylaxis. Children with anaphylaxis who have resolving symptoms and no history of asthma or previous biphasic reactions may be observed for as few as 3–4 h before emergency department discharge. Early peanut introduction reduces the risk of peanut allergy. Summary: Epinephrine remains the mainstay of anaphylaxis treatment, and adjuvant medications should not be used in its place. All patients with anaphylaxis should be prescribed and trained to use an epinephrine autoinjector. Clinically important biphasic reactions are rare. Observation in the emergency department for most anaphylaxis patients is recommended, with the duration determined by risk factors. Admission is reserved for patients with unimproved or worsening symptoms, or prior biphasic reaction.